Dr. Suriyati produces Co-TOP oil palm waste pellets as environmentally friendly and low-cost fuel - Nur Hartini, Mohd Hatta (2022)
PEKAN, 25 April 2022 – Looking at Malaysia as the world’s leading palm oil producer, a lecturer from the Faculty of Chemical and Process Engineering Technology (FTKKP), Dr. Suriyati Saleh, 39 produced Co-TOP pellet by utilising oil palm waste as an environmentally friendly and low-cost fuel.